Survey Kompetensi Guru Profesional dalam Meningkatkan Pembelajaran PJOK Tingkat SMA di Kabupaten Bekasi - Fauzi, Helmy; Gustiawati, Resti (Universitas Hamzanwadi, 2025)
Physical Education, Sport and Health (PJOK) has an important role in shaping character, improving physical fitness, and developing social and cognitive aspects of students, especially at the senior high school level. This study aims to identify and analyze the competencies of professional PJOK teachers and their impact on the quality of learning in Bekasi District. This study used a qualitative approach with purposive sampling technique, involving 30 PJOK teachers from various high schools in Bekasi District. Data were collected through questionnaires and in-depth interviews, then analyzed descriptively and thematically. The results showed that teacher competence includes four main aspects, namely pedagogic, personality, professional and social. In general, the competence of PJOK teachers in Bekasi District shows good potential, especially in building positive relationships with students and mastering learning materials. However, there are constraints in terms of ongoing training, mastery of technology, and communication with parents. This study recommends the need to strengthen professional training and support local education policies to improve the quality of PJOK learning. The findings are expected to serve as a reference in the development of teacher competency improvement programs and the establishment of a more effective and sustainable physical education ecosystem.